Pengaruh LMX Terhadap Kinerja Pegawai dengan Loyalitas dan LOC Sebagai Mediasi - Syaiful Anam; Kabul Wahyu Utomo; Handriyono (Value : Jurnal Manajemen dan Akuntansi, 2025)
Employee performance is the driving force behind organizational performance improvement. Developing an effective HR development program requires empirical evidence on how LMX, loyalty, and locus of control play a role in shaping employee performance. The research aims to explain how relational leadership shapes behavioural and psychological mechanisms that determine performance outcomes. A quantitative survey was administered to academic and administrative staff at a private university, and data were analysed using Structural Equation Modelling–Partial Least Squares. Findings show that high-quality LMX directly enhances employee performance and significantly strengthens both loyalty and internal locus of control. Loyalty functions as an emotional mechanism that reinforces commitment, whereas internal locus of control emerges as the strongest mediator, indicating that psychological empowerment plays a critical role in sustaining high performance. The results highlight the importance of supportive leadership, professional recognition, and participatory work environments in improving organisational outcomes. This study contributes to the literature by integrating relational and psychological constructs within one predictive model and by extending the application of relational leadership theories in higher education institutions. The findings offer practical insights for university management in designing leadership development, employee engagement initiatives, and performance enhancement strategies.